Insect wing tarsal foreign body causing conjunctival granuloma and marginal keratitis - Babu Kalpana; Maralihalli Rashmi (Indian Journal of Ophthalmology, 2009)
A 37 year old male was referred to our centre for management of episcleritis with peripheral keratitis in the right eye. He had a history of ocular discomfort in the right eye of 1 week duration. Slitlamp examination revealed marginal keratitis between 12′o clock to 2′o clock positions in the right eye. Lid eversion revealed an insect wing on the tarsal conjunctiva along with an adjacent conjunctival granuloma. The area of the marginal keratitis corresponded to the area of the foreign body and the conjunctival granuloma. The probable mechanism of the development of marginal keratitis and the conjunctiva granuloma is speculated in this case report.